Brazilian military policy during Dilma Rousseff's government: Discourse and practice - Mathias, Suzeley Kalil [UNESP]; Zague, Jose Augusto [UNESP]; Santos, Leandro Fernandes Sampaio (FapUNIFESP (SciELO), 2019)
This paper aims to analyze the operationalization of the Brazilian Armed Forces toward accomplishing its constitutional missions during Dilma Rousseff's government. Our sources include government speeches during the Conference of Defense Ministers of the Americas (CDMA) and the political action taken by the federal government in response to the public security situation in the city of Rio de Janeiro. The main hypothesis is that there is a difference between the government's discourse in the international arena and the domestic measures taken towards the matter, each with a different target: the first being the Armed Forces, guaranteeing their main function of defending the country and assuring that they are detached from the center of political decision-making; the second being the middle class and its demand for increased public security. The conclusion is that Rousseff's military policy resulted, in opposition to what was planned, in a higher degree of politicization of the Armed Forces followed by a bigger militarization of public security.
A política militar brasileira no governo Dilma Rousseff: O discurso e a ação
Keywords: Armed Forces; Dilma Rousseff's government; Military policy; Public security